Bioethics: the basics - Campbell, Alastair V. (Milton Park, Abingdon, Oxon : Routledge, 2013)
"Bioethics : The Basics is an introduction to the foundational principles, theories and issues in the study of medical and biological ethics. Readers are introduced to bioethics from the ground up before being invited to consider some of the most controversial but important questions facing us today. Topics addressed include: - The range of moral theories underpinning bioethics - Arguments for the rights and wrongs of abortion, euthanasia and animal research - Healthcare ethics including the nature of the practitioner-patient relationship - Public policy ethics and the implications of global and public health Concise, readable and authoritative, this is the ideal primer for anyone interested in the study of bioethics"--
Includes bibliographical references (pages 178-183) and index.
Keywords: Medical ethics; Bioethics; Social medicine; Bioethics; Ethics, Medical; Social Medicine; Bioethics; Medical ethics; Social medicine